2011
DOI: 10.1117/12.879583
|View full text |Cite
|
Sign up to set email alerts
|

A recursive cost-based approach to fracturing

Abstract: In microlithography, mask patterns are first fractured into trapezoids and then fabricated with a variable shaped beam writing machine. The efficiency and quality of the writing process is determined by the trapezoid count and external slivers. Slivers are trapezoids with width less than , a parameter determined by the mask-writing tool. External slivers are slivers whose length is along the boundary of the polygon. External slivers have a large impact on critical dimension (CD) variability and should be avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…3 Many existing fracturing approaches focus on reducing sliver length. 13,14 In addition, Spence et al have demonstrated that the number of shots is directly correlated with the write-time. 5 While there are algorithms which simultaneously minimize sliver number and length along with number of shots, 1, 2 they ignore the underlying physics behind the mask writing process; rather, they solve a simpler geometric partitioning problem by introducing rules to capture the manufacturing parameters.…”
Section: Mask Manufacturing Qualitymentioning
confidence: 99%
“…3 Many existing fracturing approaches focus on reducing sliver length. 13,14 In addition, Spence et al have demonstrated that the number of shots is directly correlated with the write-time. 5 While there are algorithms which simultaneously minimize sliver number and length along with number of shots, 1, 2 they ignore the underlying physics behind the mask writing process; rather, they solve a simpler geometric partitioning problem by introducing rules to capture the manufacturing parameters.…”
Section: Mask Manufacturing Qualitymentioning
confidence: 99%
“…A faster heuristic based on selection of rays from concave corners is also proposed by the same authors [19]. Jiang and Zakhor propose a recursive algorithm to minimize a weighted sum of shot count and slivers [15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to take more detailed specification, such as silver reduction, into account, the integer linear programming (ILP) algorithm is introduced to approach it with constraints [18]. A recursive cost-based algorithm is developed by Jiang et al to decrease the external silver length and trapezoid numbers [19]. Other than the fracturing algorithms, the mask writers also evolved from non-overlapping shots to overlapping ones so that the shot count can be reduced [20].…”
Section: Introductionmentioning
confidence: 99%